Naeso-san, a traditional herbal formula, attenuates HCl/ethanol-induced gastric injury via MAPK and NF-κB pathway modulation in mice - Choi, Suji; Ju, In Gyoung; Lee, Minji; Lee, Seungmin; Choi, Minsik; Kim, Seong Hye; Park, Seong-Hoon; Lee, Hyangsook; Jang, Young Pyo; Huh, Eugene; Oh, Myung Sook (Frontiers in Pharmacology, 2026)
BackgroundGastric ulcers affect approximately 10% of the global population, while current acid-suppressive therapies have notable limitations including impaired digestion and long-term safety concerns. Naeso-san (NSS), a traditional botanical formulation, has shown promising gastroprotective effects, yet its precise molecular mechanisms remain incompletely understood. This study investigated the molecular pathways underlying its gastroprotective effects versus conventional therapies.MethodsWe evaluated the gastroprotective effects of NSS (75, 300, 1200 mg/kg) in 7-week-old male ICR mice using a hydrochloric acid/ethanol (HCl/EtOH)-induced gastric injury model, with ranitidine (40 mg/kg) as positive control. Macroscopic damage scores were assessed, and molecular mechanisms including pro-inflammatory cytokines and mitogen-activated protein kinase (MAPK), protein kinase B (AKT), and nuclear factor-κB (NF-κB) signaling pathways were analyzed. In vitro studies using TNF-α-stimulated human gastric adenocarcinoma cell line (MKN45) gastric epithelial cells assessed inflammatory gene expression and cell viability.ResultsNSS demonstrated dose-dependent gastroprotection with superior efficacy compared to ranitidine. While ranitidine effectively reduced macroscopic damage and TNF-α mRNA expression, it showed no significant effects on IL-1β expression or JNK, p38, AKT, and NF-κB signaling pathways. In contrast, NSS significantly suppressed pro-inflammatory cytokines and comprehensively inhibited multiple molecular pathways including MAPK, AKT, and NF-κB activation across all doses. In vitro studies confirmed dose-dependent suppression of TNF-α-induced inflammatory gene expression (IL-6, IL-8, IL-1β, COX-2) without cytotoxicity.ConclusionNSS exhibits gastroprotective effects through multi-target anti-inflammatory mechanisms. These mechanistic advantages over conventional acid-suppressive therapies suggest NSS as a promising candidate for preclinical and translational studies evaluating its clinical applicability in inflammatory gastric conditions.